Your message rescues me : enhancing NDN communication quality in disaster scenarios - Cenk Gündoğan and Peter Kietzmann and Thomas C. Schmidt and Matthias Wählisch (Association for Computing Machinery, 2019)
This demo showcases how ICN resource management can service the needs of very challenged deployments such as constrained IoT edge networks in disaster scenarios. Using realistic implementations on RIOT, we demonstrate how very constrained devices in harsh environments can reliably communicate, provided QoS measures are in place. These devices gradually invoke traffic flows of different priority levels, which are displayed in real-time on a dashboard. In this setup, we contrast regular bulk traffic with degradation in flow latency and reliability with QoS-enhanced traffic differentiation and visualize the improved flow resource consumption of high priority traffic on all nodes.
Keywords: Internet of Things; Information Centric Networks; QoS